Sleep disorders in the elderly: recommendations for nursing practice - Spirgienė, Lina; Tamošaitytė, Liveta; Kučikienė, Odeta (Slauga. Mokslas ir praktika, 2022)
The most common changes in sleep in elderly are reduced sleep duration, difficulty falling asleep, altered (’shifted’) sleep time, early awakening, shorter deep sleep times and more frequent daytime sleepiness. Elderly people are 1.5 times more likely to complain of sleep disorders than younger people. Sleep quality is affected by age-related changes in the environment, psychiatric disorders and psychological factors, and side effects of medications taken. The ability of nurses to perform individual nursing plans helps to compehensive care for elderly patients, to find out the causes of insomnia, to provide information to team members, to provide non-medical interventions. The good quality of a person’s sleep helps to avoid the severe consequences of insomnia; imbalances, falls, injuries, infectious diseases. The contribution of an interdisciplinary team in the analysis of the causes of sleep disorders in eldelry is important.